A new species of Ambrysus Stål from the Central Mexican Plateau and new state records for species of the genus in the country (Heteroptera: Nepomorpha: Naucoridae) - Reynoso-Velasco, Daniel (Zootaxa, 2021)
The genus Ambrysus Stål is a species-rich genus in which multiple species groups have been proposed, including the North American Ambrysus signoreti Stål complex. The new Mexican species Ambrysus altiplanus Reynoso n. sp., which belongs to the A. signoreti complex, is described and illustrated, bringing the total number of described species of Ambrysus to 67. Also, new state records are reported for three species of the same complex, two of which are endemic to Mexico.